Analisis Perubahan Tutupan Lahan di Hutan Lindung Nggalak Rego Pasca Konsesi Pertambangan di Kecamatan Reok Kabupaten Manggarai Provinsi Nusa Tenggara Timur - Martha Tri N. Ama Doren; Ludji Michael Riwu Kaho; Norman P. L. B. Riwu Kaho (Program Studi Kehutanan, Fakultas Pertanian, Universitas Nusa Cendana, 2023)
The mining concession in the Protected Forest Area that occurred in 1994 resulted in forest ecological damage. The damage occurs by dismantling trees and soil to take the manganese in them. This research was conducted in the Nnggalak Rego RTK 103 Protected Forest Area, Reok District, Manggarai Regency, East Nusa Tenggara Province with the aim of the research being to explain changes in land cover before and after mining in the Protected Forest Area. Data analysis used in this study is a quantitative analysis that utilizes remote sensing data using satellite imagery interpretation techniques. The method used in this research is OBIS (Object Based Image Segmentation) were analyzed to determine the area of ​​land cover in 1992, 2002, 2012 and 2022 as well as changes in land cover from 1992 to 2022 in mining concession areas. The results showed that there were changes in the area of ​​protected forest in 2002, 2012 and 2022. In 1992 the mining class was 0 Ha, the mining concession entered in 1994 the forest area changed, and in 2002 the mining class was 22.14 Ha or 3.87% , in 2012 61.69 Ha or 10.78%, in 2022, 15.45 Ha or 2.70%. The cessation of mining activities in 2013 to 2022 will result in a change in land cover class, namely the dense forest class will experience an increase in area due to succession and climate that occurs in the Manggarai district. Efforts to restore protected forests to their main function, it is suggested that reclamation and rehabilitation of post-mining land should be carried out.